Sosialisasi Gerakan Gemar Menabung (GEMBUNG) Sejak Dini pada Siswa SDN 0310 Simaninggir - Hasibuan, Ebin Saleh; Yusra, Rafika; Hasibuan, Patimah; Nasution, Ali Togar; Hasibuan, Supriadi (Al-Tafani: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2025)
Socialization is a means of teaching and learning. The purpose of socialization is to provide understanding to individuals and community groups. Saving is essential in financial management. Saving is the act of setting aside money for a specific period of time for future use. Financial knowledge is not only intended for adults or parents; early childhood needs to be taught understanding and good habits that will be beneficial in the future. SDN 0310 Simaninggir, Sosopan District, Padang Lawas Regency, was the target of this activity for fourth-grade students. The main strategy in this activity was to provide students with knowledge about saving. In this learning activity, we used a medium to support the children's knowledge, namely by providing them with piggy banks.